Collaborative innovation in the public sector - Torfing, Jacob 1963- (Public management and change series, 2016)
Public sector innovation is important because the pressures of growing expectations from citizens, budget crunches, and a surge of complex governance problems cannot be solved by standard government solutions or increased funding. In order to innovate, government increasingly needs to collaborate with networks of partners across agency boundaries and especially with the nonprofit and private sectors to find new solutions. This interaction within a network can enhance creative and effective governance solutions. In this book, Jacob Torfing closely examines the link between network-based collaborative governance and innovation, proposes a framework for the study of collaborative innovation, and discusses this approach in light of theoretical insights from other disciplines and from examples of public innovation drawn from the United States, Europe, and Australia. This book will move scholars closer to being able to develop a theory of collaborative innovation